Negative Value Added and the Theory of Effective Protection - Guisinger, Stephen E. (Quarterly Journal of Economics, 1969)
I. Introduction, 415. — II. An analytical interpretation of negative value added, 425. — III. Negative value added and nonzero elasticity of substitution, 427. — IV. The measurement of effective protection when value added is negative, 430. — V. Conclusion, 432.